2012
DOI: 10.1038/hr.2012.6
|View full text |Cite
|
Sign up to set email alerts
|

Second morning urine method is superior to the casual urine method for estimating daily salt intake in patients with hypertension

Abstract: The accuracy of the casual urine (CU) method for estimating daily salt intake was compared with the second morning urine (SMU) method and with 24-h urine collection (24UC) method as the gold standard. Data were obtained from three previously reported studies, in which we evaluated the daily salt intake by the SMU method. Using SMU samples from 1315 outpatients, the estimated salt intake was lower with the CU method than the SMU method. In inpatients with a daily salt intake of 7, 8 or 18 g, the CU method was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 30 publications
4
32
0
Order By: Relevance
“…Two studies found results with Toft's equation to correlate better with 24-h urine samples compared with Tanaka's equation [31,52]. The precision of estimates seems to be influenced by the level of sodium intake [51,53], as well as the time of spot urine sampling [24,49,53]. The timing of spot urine sampling could indeed partly explain deviating results.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Two studies found results with Toft's equation to correlate better with 24-h urine samples compared with Tanaka's equation [31,52]. The precision of estimates seems to be influenced by the level of sodium intake [51,53], as well as the time of spot urine sampling [24,49,53]. The timing of spot urine sampling could indeed partly explain deviating results.…”
Section: Discussionmentioning
confidence: 90%
“…Cogswell et al [49] concluded that results obtained with Brown's equation are least biased. Using Tanaka's equation resulted in over-and underestimation of measured daily sodium excretion in various evaluation studies [31,32,[49][50][51][52][53]. Particularly, sodium excretion of women seems to be overestimated with Tanaka's equation [31,49,52], and sodium excretion of men is probably underestimated [31].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Japanese investigators including Kawasaki and Tanaka have demonstrated that it is possible to estimate 24-hrs urinary sodium from single spot urine. Using second-morning void urine, Kawasaki successfully achieve correlation of R = 0.85 between second-morning void to 24-hrs urine collection [23]. Tanaka reported a correlation of 0.65 between both methods and concluded that while spot urine is not suitable to estimate individual sodium excretion, it can be used to measure population intake of sodium [24].…”
Section: Various Methods For Determination Of Dietary Salt Intakementioning
confidence: 99%